An evaluation of the insecticidal properties of two viruses naturally associated with the bollworm, Heliothis armigera (HUBN) (Lepidoptera, Noctuidae) in South Africa - Whitlock, V. H (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1974.